Ileocaecal Tuberculosis Presenting with Massive Hematochezia: A Rare Clinical Manifestation - Neha Mehta; Man Bahadur Paudyal; Sangam Shah; Rajan Chamlagain; Moon Shrestha; Ashish Mehta; Prabin Bhattarai (Case Reports in Gastrointestinal Medicine)
Abdominal pain, diarrhea, weight loss, anorexia, and fever are common symptoms of intestinal tuberculosis, while bleeding from the lumen, intestinal obstruction, perforation, and fistula formation are uncommon presentations in ileocaecal tuberculosis. Here, we present a case of a 33-year-old male with intestinal tuberculosis who initially presented with massive bleeding per rectum.